Rezension von: Albert, Paul, Wilhelm Kraut - Hampp, Irmgard (Schwäbische Heimat, 1958)
Paul Albert, Wilhelm Kraut, vom Flaschnerbuben zum Professor - Leben und Lebenswerk. Banholzer & Co., Stuttgart-Rottweil 1956. 271 Seiten, DM 9.80